Unequal power and the dynamics of rivalry - Halvor Mehlum; Karl Ove Moene (University of Oslo, Department of Economics, 2016)
By incorporating positional dynamics into a conflict model relevant to battlefields and politics, we show that the conditions that induce regime stability can also induce hard conflicts. We show that in contests with incumbent-challenger turnover, i) asymmetric power across groups and positions may magnify conflicts; ii) more severe conflicts can occur with lower turnover of incumbents; iii) power can be self-defeating, as cost advantages can reduce payoffs; and iv) double inequality across positions and groups can maximize the graveness of conflicts and the social waste of resources. The propositions in our paper are contrary to the standard implications of static conict models.
Keywords: C73; D72; D74; 330; contests; political stability; incumbency advantage; conict and civil war